Audit committees and financial reporting quality following the government transformation program: evidence from Malaysia - Puat Nelson, Sherliza; Jamil, Nurul Nazlia (2011)
The main objective of this study is to investigate the impact of Green Book’s implementation through Government Transformation programme in improving financial reporting quality among Malaysian GLCs. Results show an agitation finding whereby no evidence was found to support the hypotheses. Nevertheless, results were significant on the year when transformations were made. Agency theory and resource dependence theory presented as the theory used to explain audit committee, as a monitoring mechanism and reduce the agency costs via gaining competitive advantage in knowledge, skills, and expertise towards financial reporting quality.However, much to my keenness,the theories were not supported hence delineating other alternative theories in gaining further understanding the relationship between audit committee and financial reporting quality. The introduction of the Green Book to strengthen the board’s effectiveness had shown otherwise. Consequently, provide some room for improvement for future research to collaborate other theoretical explanation that could explain these findings.